Women and information technology research on underrepresentation - Cohoon, J. McGrath; Aspray, William (MIT Press, 2006)
Experts investigate the reasons for low female participation in computing and suggest strategies for moving toward parity through studies of middle and high school girls, female students and postsecondary computer science programs, and women in the information technology workforce.
Keywords: Computers and women.; Sex differences in education.; Women computer scientists.; elektronické knihy; electronic books